The WET: Is it a Good Drop? - Barton, Glenton; Morgan, Annette; Pinto, Dale (Taxation Institute of Australia, 2014)
The wine equalisation tax (WET), introduced by the A New Tax System (Wine Equalisation Tax) Act 1999 (Cth), is, in essence, a wholesale sales tax on certain wine containing a specified content of potable alcohol that is sold for consumption in Australia. The apparent fiscal purpose of the Act is to reduce and recoup the public costs of alcohol abuse. The hallmarks of sound tax legislation are traditionally encapsulated in the tax policy principles of simplicity, equity, economic efficiency and fiscal adequacy. This article explores the extent to which these hallmarks are reflected in the rules of the Act. The authors conclude that the WET is not a "good tax" in light of any of the principles, and its deficiencies raise the threshold issue of whether alcohol taxation is an appropriate way to address the public costs of alcohol abuse. In the authors' opinion, there is no valid argument for its retention.